Вы находитесь на странице: 1из 17

,

, , - , . , ( ) ( ) , ( )
( ).

1.
.
, .
1 ( ). D R2 f (x, y) > 0, .

Df = { (x, y, z) | (x, y) D, 0 6 z 6 f (x, y) } R3 .


?
, ,
pi ,
D. i pi si pi .
X
f (i )si .
V =
i

, D.
X
V =
f (i )Si ,
i

Si i- . V V ,
V = inf V = sup V
.
ZZ
f (x, y) dx dy,
V =
D

, , f D.
2 ( ). N R3 ,
= (x, y, z). ,
, (x, y, z), ,
.
Pi , N , vi , i , .
X
()vi .
M=
i
1

Vi ,
N ,
X
M=
()Vi .
i

inf V = sup V

M=

ZZZ

(x, y, z) dx dy dz
N

, N .
.
. D R2 u = f (x, y) , . D = {Di } ,
Di Dj = i 6= j,

i Di = D.

si i- , = max si i = (xi , yi ) Di Di .
1.
ZZ

f (x, y) dx dy = lim
D

f (xi , yi )si ,

, f D.
f D.
, , 1, D D.
. D R3 u = f (x, y, z) , . D = {Di } ,
Di Dj = i 6= j,

i Di = D.

vi i- , = max vi i = (xi , yi , zi ) Di Di .
2.
ZZZ

f (x, y) dx dy dz = lim

f (xi , yi , zi )vi ,

, f D.
f D.
, , 2,
D D.
. , .
, . . ,
:
;
, ();


Z
f d,

.
-, .

1. , ,
.
1. f , . f ,
f . ,
Z
Z
f d.
f d =

2. f .
:
1) (.. =
= ), f
Z
Z
Z
f d .
f d +
f d =

2) c , cf
Z
Z
cf d = c f d.

3) g , f g ,
Z
Z
Z
g d.
f d
(f g) d =

4) g f 6 g ,
Z
Z
g d.
f d 6

5) |f |
Z
Z


f d 6 |f | d.

6) m 6 f 6 M ,

m6

f d
6 M.
()

2. , ,
f .
.
. 1 2, .
1. R2 :
1) y = g(x);
2) y = h(x);
3) x = a x = b.

u = f (x, y) x [a, b]
Z g(x)
f (x, y) dy.
I(x) =
h(x)

I(x) dx =

dx

f d =

dx
a

g(x)

f (x, y) dy
h(x)

g(x)

(1)

f (x, y) dy.
h(x)

3. , ,
1 2, , ,
1 2.
3. ,
0 6 x 6 a,

0 6 y 6 b,


x2 y 2
+ .
2p 2q
, ,

Z a 2
Z b
Z b 3
ZZ  2
x
a
a3 b ab3
y2 
y2 
ay 2 
ab  a2 b2 
x
dy
dx dy =
dx =
dy =
.
+
+
+
+
=
+
V =
2q
2p 2q
6p 2q
6p 6q
6 p
q
0
0
0
2p
z=

4. R .
ZZ
p
y 2 R2 x2 d.
I=

1
Z
Z R
dx
I=
R

R2 x2

R2 x2

Z
p
2
2
y R x dy = 2
2

R
R

Z
p
2
2
R x dx

R2 x2

y 2 dy.


Z R2 x2
3
1
y 2 dy = (R2 x2 ) 2 ,
3
0

Z
Z
4 R 2
32
2 R 2
2 2
(R x ) dx =
(R x2 )2 dx = R3 .
I=
3 R
3 0
45

1 .
2. (x, y) D, R3
= { (x, y, z) R3 | (x, y) D, h(x, y) 6 z 6 g(x, y) },

z = g(x, y) z = h(x, y) . u =
f (x, y, z) (x, y) D
Z g(x,y)
I(x, y) =
f (x, y, z) dz.
h(x,y)

I(x, y) dx dy =

dx dy
D

g(x,y)

f (x, y, z) dz
h(x,y)

f d =

dx dy

g(x,y)

(2)

f (x, y, z) dz.
h(x,y)

,
, , , 1.
5.
0 6 x 6 a,

0 6 y 6 b,

06z6c

u = x2 + y 2 + z 2 .
0 6 x 6 a,

0 6 y 6 b,

(z, y).
ZZZ

ZZ

(x2 + y 2 + z 2 ) dx dy dz =

(x2 + y 2 + z 2 ) dz =

dx dy

ZZ

(x2 + y 2 )c +

c3 
dx dy =
3

Z b
Z a
c3 
b3 c bc3 
a3 bc + ab3 c + abc3
abc 2 2 2
(x2 +y 2 )c+
dx
x2 bc+
dy =
dx =
+
=
(a +b +c ).
3
3
3
3
3
0
0

6. ,
x = 0,

y = 0,

z = 0,

x+y+z = 1

ZZZ

I=

1 2
Z 1
Z
I=
dx
0

dx dy dz
.
(1 + x + y + z)3

1x

dy
0

1xy

dz
.
(1 + x + y + z)3

1xy

dz
1
1
1
=

(1 + x + y + z)3
2 (1 + x + y)2 4

I=

dx
0

:
Z 1x 
1
0

1x
0

1
1
1
dy.

2 (1 + x + y)2 4

1 1
1
3 x
1
dy
=
,

2 (1 + x + y)2 4
2 x+1
4

1
I=
2

1

1
1
3 x
5
dx =

ln 2 .
x+1
4
2
8

.
( ) . ,
.
, ( ), (
) , ,
.
Rn , n = 2 3, x1 , . . . , xn Rn . u = f (x1 , . . . , xn )

Z

(3)

f d.

t1 , . . . , tn .
(4)

x1 = 1 (t1 , . . . , tn ), . . . , xn = n (t1 , . . . , tn ),
,
= { (x1 , . . . , xn ) | x1 = 1 (t1 , . . . , tn ), . . . , xn = n (t1 , . . . , tn ), (t1 , . . . , tn ) }.
, (4) ,

x1
x2
xn
.
.
.
t1
t1
t1
x2
xn
1
D(x1 , . . . , xn )
.
.
.
x
t
t
t2
2
= 2

D(t1 , . . . , tn )
. . . . . . . . . . . . . . . . . . .
x2
x1
n
. . . x
tk
k t
tk
, ..


D(x1 , . . . , xn )


J(x, t) =
D(t1 , . . . , tn )

(5)

. ,
. :

xi
tj

3. , (4), u = f (x1 , . . . , xn ) u = f (t1 , . . . , tn )


,
u = f (1 (t1 , . . . , tn ), . . . , n (t1 , . . . , tn )).

Z

f d =

J(x, t)f d ,

(6)

J(x, t) .
7. ,
y 2 = px,

y 2 = qx,

x2 = ay,

x2 = by,

0 < p < q, 0 < a < b,


RR
, d. , x y
p
p
y = 3 2 .
(7)
x = 3 2 ,
(7)
!
x

1 32 32
3 11
2 3 3

2 31 31
3
1 32 32
3

31 . (7)

p 6 6 q, a 6 6 b,
13 (q p)(b a).

,
.
. .
x = r cos , y = r sin ,

D(x, y)
=
D(r, )

x
r
y
r


cos r sin
.
sin r cos

(8)

, r, ..
, .

:
ZZ
ZZ
r dr d,
(9)
dx dy =
S =

r x y .
8. , 1
(x2 + y 2 )2 = a2 (x2 y 2 ).
,
r 2 = 2a2 cos 2.


Z
ZZ
ZZ
r dr d = 2
dx dy =
S =

a 2 cos 2

r dr = 2a
0

cos 2 d = 2a2 .

. x, y z
(x, y) r , z .
R3 . ,

x = r cos ,

x
D(x, y, z)
=
D(r, , z)

r.

r
y
r
z
r

1 .

y = r sin ,

x
z
y
z
z
z

z=z

cos r sin 0
= sin r cos 0
0
0
1

(10)

(11)

9. ,
x2 + y 2 = 2pz,

p > 0,

z = a, a > 0.
r 2 = 2pz, ,
0 6 6 2,

06r6

V =

ZZZ

dx dy dz =

ZZZ

r d dr dz =

d
0

2pa,

r2
6 z 6 a.
2p

2pa

r dr
0

a
r2
2p

dz =

= 2

2pa


r2 
dr = a2 p.
r a
2p

. r, R3 ,
x = r sin cos ,

y = r sin sin ,

z = r cos

(12)

.
x x x

sin cos
sin sin
cos
r

D(x, y, z)

y
y
r cos cos r cos sin r sin ,
= y
(13)
r

=
D(r, , )
z
z
z
r sin sin r sin cos
0
r

r 2 sin . , (12) r 6= 0, 6= 0
6= .
10. ,
(x2 + y 2 + z 2 )2 = a3 z.

r = a 3 cos ,


Z
Z
Z a
Z
3 cos
2
2
2
1
2
d
d
sin cos d = a3 .
V =4
r 2 sin dr = a3
3
3
0
0
0
0
. .
. P , = (x, y).
ZZ
(x, y) dx dy.
(14)
MP =
P

, V

R3

MV =

ZZZ

(x, y, z) dx dy dz.

(15)

.
x y
ZZ
ZZ
x(x, y) dx dy,
(16)
y(x, y) dx dy, Ky (P ) =
Kx (P ) =
P

V xy, xz yz
ZZZ
ZZZ
y(x, y) dx dy dz,
z(x, y) dx dy, dz, Kxz (V ) =
Kxy (V ) =
V
V
ZZZ
x(x, y) dx dy dz.
Kyz (V ) =

(17)

. ,

RR
RR
y(x, y) dx dy
P x(x, y) dx dy
RR
, y = RRP
.
(18)
x =
P (x, y) dx dy
P (x, y) dx dy

RRR
RRR
RRR
x(x, y) dx dy dz
y(x, y) dx dy dz
z(x, y) dx dy, dz
V
V
x = RRR
, y = RRR
, z = RRRV
.
P (x, y, z) dx dy dz
P (x, y, z) dx dy dz
P (x, y, z) dx dy dz

(19)

. x y
ZZ
ZZ
2
x2 (x, y) dx dy,
(20)
y (x, y) dx dy, Iy (P ) =
Ix (P ) =
P

x y z
ZZZ
ZZZ
2
2
(x2 + y 2 )(x, y) dx dy dz,
(y + z )(x, y) dx dy, dz, Iy (V ) =
Ix (V ) =
V
V
ZZZ
(x2 + y 2 )(x, y) dx dy dz.
Iz (V ) =

(21)


ZZZ
ZZZ
2
y 2 (x, y) dx dy dz,
(22)
z (x, y) dx dy, dz, Ixz (V ) =
Ixy (V ) =
V
V
ZZZ
x2 (x, y) dx dy dz.
Iyz (V ) =
V

. F = (Fx , Fy , Fz ) V (x, y, x) A
(, , ) m.
x
x
x
dV, dFy =
dV, dFz =
dV,
dFx =
r2
r2
r2

ZZZ
ZZZ
ZZZ
x
x
x
Fx =
dx dy dz, Fy =
dx dy dz, Fz =
dx dy dz,
(23)
2
2
r
r
r2
V
V
V

p
r = (x )2 + (y )2 + (z )2 .
4. , A , (23) .

10

2.
, , , ,
.
.
. Rn ,
A .
3. A = { A | Rn }, A , ,
Rn .
, Rn ,

,...,
.
x1
xn
, Rn
A = a1

+ + an
,
x1
xn

(24)

a1 , . . . , an x1 , . . . , xn , X. , . ,
A=X

+Y
,
x
y

(25)

X = X(x, y), Y = Y (x, y),


A=X

+Y
+Z ,
x
y
z

(26)

X, Y Z x, y, z.
4. L Rn ,
x1 = x1 (t), . . . , xn = xn (t),
A ( ), A
dxn
dx1
, . . . , an =
.
dt
dt
, L ,
.
v = (a1 , . . . , an ), = (1 , . . . , n ),
u = f (x1 , . . . , xn ), ,
v:
a1 =

()
v(f ) = lim f (+tv)f
.
t
t0

(27)


v(f ) = a1

f ()
f ()
+ + an
.
x1
xn

(28)

, A u = f (x1 , . . . , xn ) ,
A(f ) = a1

f
f
+ + an
x1
xn

(29)

11

A f . . ,
ai = A(xi ),

i = 1, . . . , n,

.
(y1 , . . . , yn ) Rn x1 , . . . , xn

x1 = x1 (y1 , . . . , yn ), . . . , xn = xn (y1 , . . . , yn ).

+ + bn
y1
yn
A .
xi
xi
ai =
b1 + +
bn ,
i = 1, . . . , n,
y1
yn

D(x1 , . . . , xn )
A=
B,
D(y1 , . . . , yn )

x1
x1
. . . y
y
n
1
D(x1 , . . . , xn )
= . . . . . . . . . . . . . .
D(y1 , . . . , yn )
xn
n
. . . x
y1
yn
B = b1

(30)

(31)

.
n
.

5. F = F (x1 , . . . , xn ) .
F
F
grad F =
+ +
.
(32)
x1 x1
xn xn
,
F
F
grad F =
+
,
(33)
x x
y y

F
F
F
grad F =
+
+
.
(34)
x x
y y
z z
, F F = const
..
, , .
6. A (24).
div A =

An
A1
+ +
.
x1
xn

(35)

, (25)
X
Y
+
,
x
y

(36)

Y
Z
X
+
+
.
x
y
z

(37)

div A =
(26)
div A =

12

+Y
+Z
x
y
z
R3 , .
A=X

7. ( ) A
 X
 Y
 Z
Y 
Z 
X 

.
(38)
rot A =
y
z x
z
x y
x
y z
. 2

=
+
+
,
x y z
.
rot A = A,

(39)

(40)

5.
. ,
div A = (, A),
(41)
,
grad F = F,

(42)

.
. .
8.
= a1 dx1 + + an dxn ,

(43)

a1 , . . . , an x1 , . . . , xn , 1- Rn .
, 1-
= A(x, y) dx + B(x, y) dy,

(44)

= A(x, y, z) dx + B(x, y, z) dy + C(x, y, z) dz.

(45)


1-, 2-, 3- .. n- Rn .
, , 2-
= X(x, y) dx dy,

(46)

2- 3-
= A(x, y, z) dx dy + B(x, y, z) dx dz + C(x, y, z) dy dz

(47)

= A(x, y, z) dx dy dz

(48)


6. n 0-
Rn .
2 .

13

i- (i + 1)-, . 0-
df (x, y) =

f
f
dx +
dy
x
y

(49)

f
f
f
dx +
dy +
dz,
(50)
x
y
z
.. . 1-
 B A 
d =
dx dy,
(51)

x
y
df (x, y, z) =

(44),
 B A 
 C
 C
A 
B 
d =
dx dy +
dx dz +
dy dz

x
y
x
z
y
z

(52)

(47).
(46) (48)

(53)

d = 0.
L,
x = x(t),

y = y(t).

1- (44) ,

dx
dy 
|L = A(x(t), y(t))
dt
+ B(x(t), y(t))
dt
dt
, (45)
x = x(t),

y = y(t),

(54)

z = z(t)



dy
dz 
dx
dt
+ B(x(t), y(t), z(t))
+ C(x(t), y(t), z(t))
|L = A(x(t), y(t), z(t))
dt
dt
dt

(55)

S R3 ,
x = x(u, v),

y = y(u, v),

z = z(u, v).

1- (45), 2- (47).
(45)
 x
 x
y
z 
y
z 
|S = A
du + A
dv,
(56)
+B
+C
+B
+C
u
u
u
v
v
v
(47)
 x z
 y z y z 
  x y x y 
x z 
+B
+C
du dv.
(57)

|S = A
u v
v u
u v
v u
u v v u
A, B C S, .. A = A(x(u, v), y(u, v), z(u, v)) ..
:
4. S R3 1-.

(d)|S = d |S .

(58)

14

, , 1-. , , (y1 , . . . , yn )
Rn x1 , . . . , xn
x1 = x1 (y1 , . . . , yn ), . . . , xn = xn (y1 , . . . , yn ).

(59)

= a1 dx1 + + an dxn = b1 dy1 + +


bn dyn .
xn
x1
+ + an
,
(60)
bi = a1
yi
yi



D(x1 , . . . , xn )
,
(61)
=
D(y1 , . . . , yn )
.
(61) :
5. u = f (x1 , . . . , xn ) (59). :
1) f x 1- (61);
2) f x y .
.
. A , i-,
(i 1)- (A), A .
2- 3-,
.

+Y
,
= a dx dy.
A=X
x
y

(X) = aY dx + aX dy.
(62)

3
A = X x + Y y + Z z R
= a dx dy + b dx dz + c dy dz

(63)

2-,
(A) = (aY + bZ) dx + (aX cZ) dy + (bX + cY ) dz.
= a dx dy dz 3-,
(X) = aZ dx dy aY dx dz + aX dy dz.

3. A = X x
+Y

(64)
(65)

+ Z z

= dx dy dz.
A 1-

(66)

A = X dx + Y dy + Z dz.

dA = (rot A),
rot A (38).
9. (66) R3 .

(67)

15

, . .
= a dx + b dy + c dz 1-,
 a
a
a
X
Y
Z 
dx+
+Y
+Z
+a
+b
+c
A() = X
x
y
z
x
x
x
 b
b
b
X
Y
Z 
+ X
dy+
+Y
+Z
+a
+b
+c
x
y
z
y
y
y
 c
c
c
X
Y
Z 
+ X
dz. (68)
+Y
+Z
+a
+b
+c
x
y
z
z
z
z
2- = a dx dy + b dx dz + c dy dz
 a
a
a
X
Y
Z
Z 
A() = X
dx dy+
+Y
+Z
+a
+a
+b
c
x
y
z
x
y
y
x
 b
b
b
Y
X
Z
Y 
+ X
dx dz+
+Y
+Z
+a
+b
+b
c
x
y
z
z
x
z
x
 c
c
c
X
X
Y
Z 
+ X
dy dz. (69)
+Y
+Z
a
+b
+c
+c
x
y
z
z
y
y
z
, 3- = a dx dy dz
 a
a
a
X
Y
Z 
dx dy dz.
(70)
+Y
+Z
+a
+a
+a
A() = X
x
y
z
x
y
z
, i- i-.

 a
 b
a
X
Y 
b
X
Y 
A() = X
dx + X
dy.
(71)
+Y
+a
+b
+Y
+a
+b
x
y
x
x
x
y
y
y

 a
a
X
Y 
dx dy.
(72)
+Y
+a
+a
A() = X
x
y
x
y
(70) , :
4.
.

A() = (div A) ,

(73)

, :
6. A
A() = d((A)) + (d)(A).

(74)

3.
.
10. L R2 , x = x(t),
y = y(t), t [t0 , t1 ], = A dx + B dy 1-.
Z t1 
Z t1
dx
dy 
A(x(t), y(t))
dt
(75)
+ B(x(t), y(t))
|L =
dt
dt
t0
t0
L.

16

11. L R3 , x = x(t),
y = y(t), z = z(t), t [t0 , t1 ], = A dx + B dy + C dz 1-.
Z t1 
Z t1
dx
dy
dz 
dt
(76)
A(x(t), y(t), z(t))
+ B(x(t), y(t), z(t))
+ CB(x(t), y(t), z(t))
|L =
dt
dt
dt
t0
t0
L.

L
Z
.
L

. , ..
= (x, y) R2
F = (A, B) Fx = A(x, y)
R
Fy = B(x, y). L A dx + B dy
F , L R2 .
= A dx + B dy + C dz
L R3 .
. (75)

Z t1
Ax + By p 2
p
(x ) + (y )2 dt
(x )2 + (y )2
t0
, f (t).

Z t1
f (t) ds,
(77)
t0

ds =

(x (t))2 + (y (t))2 dt.

(78)

ds, (78), , , (77),


( (75),
).
, f = 1,
Z t1 p
Z
(x (t))2 + (y (t))2 dt
(79)
ds =
t0

L.
,
Z t1
Z
p
f (t) (x (t))2 + (y (t))2 + (z (t))2 dt,
f (t) ds =
(80)
t0


Z t1 p
Z
ds =
(x (t))2 + (y (t))2 + (z (t))2 dt
L

t0

(81)

17

12. S R3 ,
x = x(u, v), y = y(u, v), z = z(u, v), (u, v) R2 , R2 ,
= A dxdy + B dxdz + C dydz 2-.
ZZ
ZZ
A(x(u, v), y(u, v), z(u, v))xy +
|S =


+ B(x(u, v), y(u, v), z(u, v))xz + C(x(u, v), y(u, v), z(u, v))yz dudv,
(82)

xy , xz yz
 x
 x y 
u
u ,
u
y
x
x
v

z
u
z
v

 y

u
y
v

z
u
z
v

, S.

. (82)

ZZ
Axy + Bxz + Cyz q 2
q
xy + 2xz + 2yz dudv
(83)
2
2
2

xy + xz + yz
, f (u, v).
ZZ
f (u, v) dS,
(84)

dS =

2xy + 2xz + 2yz dudv.

(85)

dS, (85), ,
, (84)
( (82), ).
, f = 1,
ZZ
dS
(86)

4.

4. ()
7.